Exchange rate pass-through, domestic competition, and inflation: Evidence from the 2005/08 revaluation of the Renminbi - Raphael A. Auer (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper quantifies the effect of the government-controlled appreciation of the Chinese renminbi (RMB) vis-à-vis the USD from 2005 to 2008 on the prices charged by US producers. As the RMB during that time was pegged to a basket of currencies, the empirical strategy must account for the fact that the currencies included in the basket may have directly affected US prices. Thus, the pre-2005 period is used to filter out the effects of other exchange rates on import and producer prices. Additionally, utilizing the remainder of the sample, the pure effect of an RMB appreciation on US import prices and, in turn, the effect of RMB-induced US import price fluctuations on US producer prices is established. In a panel spanning the period from 1994 to 2010 and including 417 manufacturing sectors, the main finding emerging from this empirical strategy is that import prices pass into producer prices at an average rate of 0.7. This finding supports the view that the markets for domestic and imported manufactured goods are well integrated. Consequently, even if the exchange rate affects import prices only to a small extent, it may have a substantial impact on inflation, as it exerts a sizeable impact on the competitive environment of domestic producers and the prices that they charge.
Keywords: F11; F12; F14; F15; F16; F40; E31; L16; 330; price complementarities; exchange rate pass through; China; inflation; markups; Exchange Rate Pass-Through; Außenhandelspreis; Wettbewerb; Mark-up Pricing; Inflation; Schätzung; USA; Renminbi; Aufwertung; China